An Energy-Efficient Based Secure IOT Data Transfer with Hashed Data Access Policy Using ACROT-DHSKECC and LSCRC32 - Anjikumar, Tamarapalli; Chakravarthy, A.S.N. (Journal of Telecommunications and the Digital Economy, 2025)
The rapid expansion of Internet of Things (IoT) applications in healthcare has amplified the need for secure, efficient, and scalable data transmission frameworks. This study proposes an energy-aware and secure IoT-based data transmission architecture tailored for remote healthcare monitoring systems. Unlike conventional encryption-centric models, the proposed framework integrates lightweight double encryption (ACROT-DHSKECC) and hashed access control (LSCRC32) with optimised network path selection using clustering and Grasshopper Optimisation Algorithm (GOA). This integration reduces latency, enhances node-level energy efficiency, and secures data transmission over distributed networks. The system’s design aligns with next-generation telecom infrastructure, making it well-suited for deployment in 5G-enabled smart healthcare environments. Simulation results demonstrate reduced hash generation time, lower memory usage, and enhanced encryption performance, affirming its viability for secure data delivery in modern digital health ecosystems.